Uresničevanje načela kontradiktornosti v postopku odločanja o izdaji in o odvzemu dovoljenja za pridobitev kvalificiranega deleža v zavarovalnici - Žuber, Bruna (Javna uprava, 2017)
One of the tasks of Insurance Supervision Agency, which aims to control corporate governance of insurance undertakings, is to decide on issuing and on withdrawal of the authorization for acquiring qualifying holding in an insurance undertaking. The effects of the Agency%s decision are not limited only to legal implications but also to economic. Therefore, unlawful decision of the Insurance Supervision Agency regarding qualifying holding in an insurance undertaking may cause a difficult to repair damage for companies that are or intend to become qualified holders. All of the above and underlying the fact that the judicial review of decisions of the Insurance Supervision Agency is limited, indicates that the Insurance Supervision Agency in procedures regarding issuing or withdrawing the authorization for acquiring qualifying holding in an insurance undertaking is expected to act diligent from the procedural point of view and in this context to implement the right to be heard in all its dimensions.
Keywords: implementation of adversarial principle; kvalificiran delež v zavarovalnici; nadzor; posebni upravni postopek; pravica do izjave; pravica do obrazložitve; qualifying holding in an insurance undertaking; right to be heard; right to reasons for the decision; special administrative procedure; uresničevanje načela kontradiktornosti; zavarovalnice